2021
DOI: 10.3390/rs13040557
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Temporal Small Baseline Interferometric SAR Algorithms: Error Budget and Theoretical Performance

Abstract: Multi-temporal interferometric synthetic aperture radar (MT-InSAR) techniques are well recognized as useful tools for detecting and monitoring Earth’s surface temporal changes. In this work, the fundamentals of error noise propagation and perturbation theories are applied to derive the ground displacement products’ theoretical error bounds of the small baseline (SB) differential interferometric synthetic aperture radar algorithms. A general formulation of the least-squares (LS) optimization problem, representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…In this work, we refer to a unified representation of the SB algorithms. Indeed, the different implementations of the SB methods proposed in the literature have individual peculiarities; however, they can almost be unified [47], [66] considering they solve a linear optimization problem that relates the vector of the (known) unwrapped ML SB interferograms, namely , to a model of unknown parameters of the ground deformation . The adopted unified representation of the SB linear transformation is as follows: (18) where is the design matrix of the considered linear transformation.…”
Section: Sb Multi-temporal Insar Methodsmentioning
confidence: 99%
“…In this work, we refer to a unified representation of the SB algorithms. Indeed, the different implementations of the SB methods proposed in the literature have individual peculiarities; however, they can almost be unified [47], [66] considering they solve a linear optimization problem that relates the vector of the (known) unwrapped ML SB interferograms, namely , to a model of unknown parameters of the ground deformation . The adopted unified representation of the SB linear transformation is as follows: (18) where is the design matrix of the considered linear transformation.…”
Section: Sb Multi-temporal Insar Methodsmentioning
confidence: 99%
“…It is calculated for each coherent DS target, the (unknown) displacement time-series [28]. A recent study [23] on the theoretical accuracy of the SB methods and the SBAS technique, in particular, showed how ground deformation error bounds are in general agreement with the result of quantitative analyses that showed that the accuracy of SBAS measurements is on the order of 1 mm yr −1 and 3-5 mm, for the ground deformation velocity and each data measurement, respectively. Additional recent advancements of the methods based on distributed target deformations can be found in [37,[39][40][41][42].…”
Section: Multi-temporal Dinsar Technologies and Sbas Methodsmentioning
confidence: 99%
“…The principal results of the investigations performed within our Dragon IV project have been published in peer-reviewed journals over the last five years [14][15][16][17][18][19][20][21][22][23][24][25][26][27] and represent the starting point for future studies to be performed in the following years. We will summarize the main results of previous research related to this project in this article.…”
Section: Introductionmentioning
confidence: 99%
“…A recent work [44] comprehensively addressed, from the theoretical perspective, the problem of deriving some bounds for the relative errors of Mt-InSAR SB products. In particular, using the basic principles of perturbation and error propagation theory [45][46][47], it has been shown that the expected relative error ε v of the computed vector v (i.e., the solution of the least-squares problem of Equation ( 1)) is given by:…”
Section: Sbas Deformation Measurement Accuracymentioning
confidence: 99%
“…Toward that aim, the average spatial coherence of the chosen interferograms and the connectivity of their network were taken into account at the same time. Our work benefits from the primary outcomes of a recent investigation [44] that addressed the error budget analysis of SB Mt-InSAR techniques.…”
Section: Introductionmentioning
confidence: 99%